Pengaruh Personal Branding, Perceived Value, dan Product Quality terhadap Keputusan Pembelian Kerajinan Rajut pada Home Industri Carolline Crafty Crochet di Petunjungan Kabupaten Brebes - Deajeng Carolline Firisqi Samudera Sari; Yugi Setyarko (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of Personal Branding, Perceived Value, and Product Quality on consumer purchasing decisions for Carolline Crafty Crochet home industry knitting craft products. The background of this study is based on the increasing competition in the handicraft business, so that business owners are required to be able to build a strong personal image, provide perceived value to consumers, and maintain product quality to increase purchasing attractiveness. The data source used is primary data obtained through distributing questionnaires to respondents. The population of this study were consumers who had purchased Carolline Crafty Crochet products both offline and online. The sampling technique used a nonprobability sampling method with a purposive sampling approach. The calculation of the number of samples used the Lemeshow formula and obtained 96 respondents who met the research criteria. Data analysis was carried out with the help of SPSS version 27 software through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and partial and simultaneous hypothesis testing. The results showed that the variables Personal Branding, Perceived Value, and Product Quality had a positive and significant effect on consumer purchasing decisions. This indicates that the stronger the business owner's personal branding, the higher the perceived value felt by consumers, and the better the quality of the products offered, the greater the likelihood of consumers making purchasing decisions. These findings provide practical implications for small and medium enterprises (SMEs), particularly in the handicraft industry, that marketing strategies based on personal branding, increasing perceived value, and controlling product quality need to be optimized to increase consumer loyalty and purchasing interest. Thus, this study emphasizes the importance of integrating aspects of personal branding, perceived value, and product quality in shaping purchasing decisions, which can serve as a reference for developing sustainable business strategies in today's competitive era.